2010
DOI: 10.1371/journal.pone.0009886
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Mediated Self-Assembly of Artificial Vesicles

Abstract: BackgroundAlthough multicompartment systems made of single unilamellar vesicles offer the potential to outperform single compartment systems widely used in analytic, synthetic, and medical applications, their use has remained marginal to date. On the one hand, this can be attributed to the binary character of the majority of the current tethering protocols that impedes the implementation of real multicomponent or multifunctional systems. On the other hand, the few tethering protocols theoretically providing mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 66 publications
2
67
0
Order By: Relevance
“…Biotinylated DNA has been attached to biotinylated lipids within liposomes and lipid-coated emulsions using streptavidin cross-linkers (Fig. 3d) [67][68][69]. The challenge here is that streptavidin can directly cross-link biotinylated particles [26].…”
Section: Other Modificationsmentioning
confidence: 99%
“…Biotinylated DNA has been attached to biotinylated lipids within liposomes and lipid-coated emulsions using streptavidin cross-linkers (Fig. 3d) [67][68][69]. The challenge here is that streptavidin can directly cross-link biotinylated particles [26].…”
Section: Other Modificationsmentioning
confidence: 99%
“…For example, it has been reported that lipid compartments can form clusters following simple adhesive forces [28,14]. Protein synthesis is still possible in such assemblies [27], and the idea of prototissue has been put forward, as supported by some pioneer work on membrane-to-membrane connective mojeties [49,42].…”
Section: Semi-synthetic Minimal Cells (Ssmcs)mentioning
confidence: 99%
“…In the context of guiding the assembly of supramolecular compartments, the ssDNA oligonucleotides anchored to the surface of the compartments were shown to act as biomolecular combination locks, linking exclusively compartments that display complementary sequences. Using ssDNA oligonucleotides as 'smart glue' therefore allowed the programmable linkage of both hard [5,6,23,51,68,78,85] and soft colloids [3,19,29,31,32,50,71,72]. As demonstrated in Magnusson et al [48] even the entire compartment (in this case a small micelle) can be assembled and disassembled via DNA strand displacement.…”
Section: Programmable Nano-bioreactors For Synthetic Biologymentioning
confidence: 99%
“…Other studies employed supramolecular nanoscale and microscale compartments as "nano-bioreactors" that result from the non-covalent interaction of molecules (i.e., primary self-assembly process) [1,[53][54][55]63]. Several protocols have been established to control the self-assembly of these compartments into higher-order structures (i.e., secondary self-assembly process) [3,30,32] as well as to induce budding [10] and fusion [17,61,75]. Even protocols for internal compartmentalization of artificial vesicles have been reported [9,11,36,40,43,86].…”
Section: Introductionmentioning
confidence: 99%